(3CSGSjGJ fXe GdeYdheGJ GdeMGSHjI hJcfhdhLjG GdeYdheGJ (B/s - (3GdOdGgeI, SdjeGf eUWais ((3YeGf(B: s (3eDSSI GdhQGb(B, s, 2007)
(3GdeONd Gdi fXe GdeYdheGJ, OhQ GdeYdheGJ GdeMGSHjI hbjeI GdeYdheGJ aj GJNGP GdbQGQGJ aj Xd XQha GdJCcO GdeNGWQI hYOe GdJCcO, fXe GdeYdheGJ GdeMGSHjI hGgejI GSJNOGe GdMGSH GdGdj, fXe GdeYdheGJ GdeMGSHjI hGdJNWjW, fXe GdeYdheGJ GdeMGSHjI hGdQbGHI, GWGQ fXe GdeYdheGJ GdeMGSHjI GdGOGQjI, eMGSHI GdJcGdja cfXGe dJTZjd GdHjGfGJ, JMdjd GdJcdaI GdefaYI aj Jbjje GdfXe, JcfhdhLjG GdeYdheGJ hGdGJUGdGJ, COhGJ GdJMdjd fXe GdeYdheGJ, GOGQI bhGYO GdHjGfGJ, GSJNOGe HQfGeL GcSd aj GYOGO GdSLdGJ hGdJbGQjQ GdeMGSHjI hJMdjd GdJcGdja, GSJNOGe HQfGeL GcSd aj GYOGO GdbhGFe GdeGdjIs
Keywords: (3GdeMGSHI JGeGdjIs; (3GdeYdheGJs; (3JGJcfhdhLjGs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s